Why Godse Killed Gandhi - V T Rajshekar; RAJSHEKAR (V T) (New Delhi Gyan Publishing House, 2015)
Partition of India brought immense benefit to the Aryan upper castes, particularly the vaidiks who became the ruling class of India. If India was not partitioned then there was no question of a vaidik (Jawaharlal Nehru) becoming the first Prime Minister of India and the brahminical exploitation reaching it climax. The credit for transferring the power from the British to the Brahmins, by cunningly voiding the Muslim hindrance through partition, goes to none else but Gandhi. That is how the practical-minded vaidiks led by Nehru goaded Gandhi to secretly support partition though as a typical Hindu Gandhi spoke one thing but acted against it. Gandhi quietly schemed at partition and the honest Brahmin in Godse mis took Gandhi believing his words that Gandhi was sincerely against partition though in fact he colluded in dividing India and that is why Godse killed him.
Keywords: India; Politics and government; Gandhi, Mahatma, 1869-1948; Assassination; Godse, Nathuram Vinayak, 1912-1949; Islam; Brahmans; Conspiracies